Degradación de nitrofenoles en solución acuosa con persulfato térmicamente activado - Díaz Cubilla, Felicia Mabel (2014)
Phenolic compounds are considered hazardous waste released into the environment by industries such as steel, petrochemicals and pharmaceuticals. Here, we propose the degradation of nitrophenols in aqueous solutions by Advanced Oxidation Technologies by the use of sodium persulfate (PS) as an oxidant. Degradation of nitrophenols (2-nitrophenol, 4-nitrophenol and 2,4-dinitrophenol) in aqueous solution, by thermal activation of PS was studied. In our experimental conditions, total degradation of nitrophenols was achieved in 45 minutes. However, Total Organic Carbon (TOC) values reached 84 ± 3% after 180 minutes, showing that mineralization was high but not complete. A reaction mechanism of sulfate (SO4 .-) radicals with nitrophenols was proposed